A Confirmatory Factor Analysis Model of Academic Service-Learning Principles used in The Institute of Vocational Education in Thailand - Chantana Potikruprasert; Pariyaporn Tungkunanan; Siripan Choomnoom (My University, 2019)
Abstract The principle of service is at the heart of the academic service-learning of the Institute of Vocational Education, Bangkok, in Thailand. Therefore, the confirmatory factors of this academic service-learning were studied. The purpose of the research is to study the factors of academic service-learning principles. The results of the analysis of the confirmatory factors of the academic service-learning principles and the professions of the Institute of Vocational Education, Bangkok, were consistent with the empirical evidence. After the standard factors were considered, it was found that there were 5 confirmatory factors:; the principle of trustworthiness, the principle of confidence, the principle of instant response, the principle of regard, and the principle of objectiveness. The values of the factors were 0.84, 0.92, 0.90, 0.92, and 0.89, respectively. The statistical significance of all factors was .05
Keywords: Trustworthiness; Service-Learning and Community Engagement